Penafsiran Lafaz al-Rih dan al-Riyah dalam Al-Qur’an - Furqan Furqan; Nabilla Ummami (TAFSE: Journal of Qur'anic Studies, 2018)
One form of the beauty of the language and the richness of the meaning of the Qur'an is the use of the words rih and riyah, which are the same word with different forms of derivation but have a different philosophies of meaning. Even in Surah Yunus verse 22 and three other verses, the Qur'an mentions the word rih for both positive and negative connotations. The use of such words seems to give the reader the impression that the Qur'an is inconsistent in choosing the words it uses. Departing from this problem, the author formulates two objectives of this research, namely to explain the classification and scope of meaning of the words rih and riyah in the Qur'an and to describe the interpretation of the mufassir related to these lafaz. From the results of the study, lafaz rih has several expressions of meaning according to the context of the intended verse, namely punishment, strength or glory, help and fragrant smell. Broadly speaking, the word riyah is interpreted to be more about things that are fun and welfare information, because of the magnitude and many benefits the Qur'an mentions in the plural. As for the scientific interpretation of the word rih, the Qur'an describes something that is harmful and destructive. This is because at a certain speed the wind can exceed the benefit as well as the description of the commentators about the hot wind that brings fire and burns to destroy anything in its path. Salah satu bentuk keindahan bahasa dan kekayaan makna Alquran yaitu penggunaan kata rih dan riyah yang merupakan satu kata yang sama dengan bentuk derivasi yang berbeda, namun mempunyai filosofi makna yang berbeda. Bahkan dalam surah Yunus ayat 22 dan tiga ayat lainnya, Alquran menyebutkan kata rih untuk konotasi yang positif maupun negatif. Pemakaian kata serupa itu seakan-akan memberi kesan kepada pembaca bahwa Alquran inkonsisten dalam memilih kata-kata yang digunakannya. Berangkat dari permasalahan ini, penulis merumuskan dua tujuan penelitian ini yaitu untuk menjelaskan klasifikasi dan cakupan makna dari kata rih dan riyah dalam Alquran dan mendeskripsikan penafsiran mufassir terkait dengan lafaz tersebut. Dari hasil penelitian tersebut, lafaz rih memiliki beberapa ungkapan makna sesuai dengan konteks ayat yang dituju yaitu azab, kekuatan ataupun kejayaaan, petolongan dan bau harum. Secara garis besar, kata riyah ditafsirkan lebih kepada hal-hal yang sifatnya informasi-informasi menyenangkan dan kesejehteraan, karena besar dan banyak manfaatnya Alquran menyebutkannya dalam bentuk jamak. Adapun pada penafsiran ‘ilmi kata rih, Alquran mendeskripsikan sesuatu  yang merugikan dan merusak. Hal ini karena pada kecepatan tertentu angin dapat melampaui kemaslahatan seperti halnya uraian para mufassir mengenai angin panas yang membawa api dan membakar hingga membinasakan apapun yang dilaluinya.